Principal Leadership in the Digital Era: A Systematic Literature Review - Besse Desi Amelia (Universitas Negeri Makassar, 2026)
This study aims to comprehensively analyze principal leadership in the digital era. The method used is a Systematic Literature Review (SLR) with reference to the PRISMA guidelines. Of the 400 identified articles, 15 selected articles were analyzed thematically to answer three research questions. The results show that principal leadership in the digital era is characterized by a clear digital vision, an adaptive attitude towards technological change, and a transformational approach in building school culture. The main strategies implemented include developing teacher digital literacy, digitizing learning and school administration, and strengthening character education based on moral and religious values. However, digital leadership still faces challenges such as limited infrastructure, low teacher digital competence, and human resource readiness. The implications of this study emphasize the importance of strengthening principal leadership capacity as a key factor in the success of sustainable digital transformation in education that is oriented towards quality learning.